Β-hCG promotes epithelial ovarian cancer metastasis through ERK/MMP2 signaling pathway. Issue 1 (2nd January 2019) - Wu, Weimin; Gao, Hao; Li, Xiaofeng; Peng, Shumin; Yu, Jing; Liu, Na; Zhan, Guangxi; Zhu, Yong; Wang, Kai; Guo, Xiaoqing
ABSTRACT: Epithelial ovarian cancer (EOC) is the most lethal gynecologic malignancy, with typically extensive intraperitoneal implantation leading to poor prognosis. Our previous study preliminarily demonstrated β-hCG can promote tumorigenesis in immortalized nontumorigenic ovarian epithelial cells. In this study, the roles and mechanisms of β-hCG in regulating EOC proliferation and metastasis were thoroughly explored. First, histologically, β-hCG was aberrantly overexpressed in human EOC metastatic tissues, and significantly correlated with FIGO stage, tumor size, differentiation, histologic grade and high grade serous ovarian carcinoma (HGSOC) ( P < 0.05). However, serologically, β-hCG expression showed no significant difference between EOC and nonmalignant ovarian patients. Second, β-hCG was confirmed to have no significant effects on EOC proliferation in vitro and in vivo, while β-hCG upregulation was proven to promote migration and invasion ability in ES-2 and OVCAR-3 cells in vitro ( P < 0.05), and β-hCG downregulation in SKOV3 cells had the opposite effect. Moreover, more invadopodia protrusions, mitochondria accumulations and cytoskeletal rearrangements were observed in β-hCG-overexpressing ES-2 cells, while β-hCG-depleted SKOV3 cells produced the opposite effect. Furthermore, β-hCG was confirmed to clearly facilitate intraperitoneal metastasis in nude mouse orthotopic ovarian xenograft models. Importantly, these effects of β-hCG were mediated by activation of the ERK/MMP2 signaling pathway, independently of luteinizing hormone/chorionic gonadotropin receptor (LHCGR) presence, and inhibition the pathway with the p-ERK1/2 inhibitor SCH772984 significantly impaired the tumor-promoting effects induced by β-hCG. Collectively, these data provide new insight into the roles and mechanisms of β-hCG in regulating EOC metastasis through ERK/MMP2 signaling pathway and may become a new target for therapeutic intervention.